Pengaruh Kampanye di Instagram dengan Penggunaan Kain Tradisional pada Gen Z - Sandy M., Bagus Kurnia; Claretta, Dyva (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out whether the #BerkainituKeren campaign carried out by the Pemuda Berkain Surabaya has a significant influence on the use of traditional fabrics in generation z followers of the Instagram account @pemudaberkain.sub. This study uses quantitative methods to determine causal relationships or is called association-correlation type research. The sampling technique uses simple random sampling using Google Forms in the data collection process. Data processing is done with the help of SPSS and Microsoft Excel. Based on the results of the study concluded that the #BerkainituKeren campaign had a significant influence on the use of traditional cloth in generation z on Instagram @pemudaberkain.sub. Keywords: campaign; use of tradisional fabrics; Pemuda Berkain Surabaya; generation z